Comparison of the Iranian and Scandinavian bachelor of nursing curriculum (Sweden): A scoping review - Majid Purabdollah; Vahid Zamanzadeh; Leila Valizadeh; Akram Ghahramanian; Saeid Mousavi; Mostafa Ghasempour (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: The comparison of the educational curriculum improves the content and quality of the curriculum and needs to be revised and modified in line with the current needs of society. Development of nursing knowledge, the emergence of emerging diseases requires that the nursing curriculum be codified and provide the necessary skills to provide quality and safe care. MATERIALS AND METHODS: The study aimed to Comparison of Iranian and Scandinavian Bachelor of Nursing Curriculum (Sweden). This descriptive-comparative study was conducted based on the Bereday model in four stages: Description, Interpretation, Juxtaposition, Comparison, and Analysis in 2022. We use relevant electronic databases such as PubMed, CINAHL, Web of Science, Iran Medex, SID, Magiran, Google Scholar, Iran Doc, and Science Direct databases. RESULTS: The results showed that despite the similarities, the Swedish nursing curriculum had special features in most of the mentioned dimensions. Including decentralized admission, Fits the need, competency-based curriculum, attention to holistic care and intercultural care, use of new digital technologies in education, and clinical training and evaluation. CONCLUSION: It seems that the Iranian nursing curriculum is far from the mentioned perspective. Using the experiences of the world's top universities, such as Sweden, can improve the quality of nursing undergraduate programs and improve the nursing profession by eliminating current shortcomings.